Deconstructing compassionate conservation. Issue 4 (8th July 2019) - Hayward, Matt W.; Callen, Alex; Allen, Benjamin L.; Ballard, Guy; Broekhuis, Femke; Bugir, Cassandra; Clarke, Rohan H.; Clulow, John; Clulow, Simon; Daltry, Jennifer C.; Davies‐Mostert, Harriet T.; Fleming, Peter J. S.; et al.
Abstract: Compassionate conservation focuses on 4 tenets: first, do no harm; individuals matter; inclusivity of individual animals; and peaceful coexistence between humans and animals. Recently, compassionate conservation has been promoted as an alternative to conventional conservation philosophy. We believe examples presented by compassionate conservationists are deliberately or arbitrarily chosen to focus on mammals; inherently not compassionate; and offer ineffective conservation solutions. Compassionate conservation arbitrarily focuses on charismatic species, notably large predators and megaherbivores. The philosophy is not compassionate when it leaves invasive predators in the environment to cause harm to vastly more individuals of native species or uses the fear of harm by apex predators to terrorize mesopredators. Hindering the control of exotic species (megafauna, predators) in situ will not improve the conservation condition of the majority of biodiversity. The positions taken by so‐called compassionate conservationists on particular species and on conservation actions could be extended to hinder other forms of conservation, including translocations, conservation fencing, and fertility control. Animal welfare is incredibly important to conservation, but ironically compassionate conservation does not offer the best welfare outcomes to animals and is often ineffective in achieving conservation goals. Consequently, compassionate conservation may threaten public and governmental support for conservation because of the limited understanding of conservation problems by the general public. Abstract : Article impact statement : Compassionate conservation has an arbitrary focus on mammals, lacks compassion, and offers ineffective conservation solutions. Abstract : Deconstrucción de la Conservación Compasiva Resumen: La conservación compasiva se enfoca en cuatro principios: no causar daño; los individuos importan; la integración de los animales individualmente; y la coexistencia pacífica entre los humanos u los animales. Recientemente, la conservación compasiva ha sido promovida como una alternativa a la filosofía convencional de la conservación. Creemos que los ejemplos presentados por los conservacionistas compasivos han sido elegidos arbitraria o deliberadamente por estar enfocados en los mamíferos; por ser inherentes y no compasivos; y por ofrecer soluciones de conservación poco efectivas. La conservación compasiva se enfoca arbitrariamente en las especies carismáticas, principalmente los grandes depredadores y los megaherbívoros. La filosofía no es compasiva cuando deja que los depredadores invasores dentro del ambiente causen daño a un vasto número de individuos nativos o usa el miedo al daño por superdepredadores para aterrorizar a los mesodepredadores. El entorpecimiento del control de especies exóticas (megafauna, depredadores) in situ no mejorará las condiciones de conservación de la mayoría de la biodiversidad, incluso si los conservacionistas compasivos no dañan a los individuos exóticos. Las posiciones que toman los llamados conservacionistas compasivos sobre especies particulares y sobre las acciones de conservación podrían extenderse para entorpecer otros tipos de conservación, incluyendo las reubicaciones, el encercado para la conservación y el control de la fertilidad. El bienestar animal es increíblemente importante para la conservación e irónicamente, la conservación compasiva no ofrece los mejores resultados de bienestar para los animales y comúnmente es poco efectiva en el logro de los objetivos de conservación. Como consecuencia, la conservación compasiva puede poner en peligro el apoyo público y del gobierno que tiene la conservación debido al entendimiento poco limitado que tiene el público general sobre los problemas de conservación. 摘要: 同理心保护注重四项原则: 不制造伤害、心系每一条生命、不排斥每一种动物, 以及人与动物和平共处。目前, 同理心保护已经被推崇为传统保护哲学的替代选择。然而, 我们认为同理心保护主义者有意或武断地挑选了哺乳动物作为范例, 这在本质上并不具备同理心, 且他们提供的保护方案也不实际。同理心保护常常不加判断地只关注明星物种, 尤其是大型食肉动物和食草动物;若是保留环境中的入侵食肉动物, 从而对原生种造成巨大伤害, 抑或是利用顶级捕食者来威慑中等食肉动物, 这样的保护理念实际上都没有同理心。即便同理心保护主义者没有直接伤害外来物种的个体, 阻止对外来物种 (大型动物、食肉动物) 的就地种群控制, 也不能改善组成生物多样性的大部分物种的保护情况。所谓的同理心保护主义者对特定物种或是特定保护行动所采取的立场, 甚至会阻碍其它形式的保护, 如迁地保护、围栏保护和繁殖控制等。动物福利对保护极为重要, 然而讽刺的是, 同理心保护不仅没有给动物提供最优的福利条件, 还通常不利于实现保护目标。因此, 鉴于公众对保护问题的认知有限, 同理心保护可能会威胁到公众和政府对保护的支持。翻译: 胡怡思; 审校: 聂永刚